2023
DOI: 10.5603/cj.a2022.0075
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed therapy to treat intermediateand high-risk pulmonary embolism: Personal experience and review of the literature

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Cardiology Journal" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Of note 40% (38 patients) of IHRPE patients were referred for CDT as the primary reperfusion option. In this group time between PE diagnosis and CDT was 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) hours.…”
Section: Patient Characteristicsmentioning
confidence: 77%
See 1 more Smart Citation
“…Of note 40% (38 patients) of IHRPE patients were referred for CDT as the primary reperfusion option. In this group time between PE diagnosis and CDT was 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) hours.…”
Section: Patient Characteristicsmentioning
confidence: 77%
“…There is growing clinical evidence on catheter-directed therapies (CDT) for the treatment of acute PE. Currently a wide range of systems and techniques for CDT are available including clot fragmentation, mechanical embolectomy, local thrombolysis, and combined pharmaco-mechanical thrombus fragmentation [5][6][7]. A multicenter, investigator initiated European Database on Catheter Directed Therapy of Pulmonary Embolism (EuroPE-CDT) has been organized in order to assess the currently applied CDT techniques in real life and to determine in--hospital mortality, efficacy and safety of this invasive procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaner XT TM is a 6 F rotational thrombectomy system, utilizing a sinuous-shaped radio-opaque wire that rotates at approximately 4000 rounds per minute, facilitating gentle mechanical declotting [ 21 ]. Details of the CDTx methods applied by our PERT have previously been described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…CDT should also be considered in patients in whom ST has not been effective. A recent meta-analysis showed that CDT can reduce the risk of in-hospital death [30] compared with ST.…”
Section: Catheter-directed Treatment In the Management Algorithm For ...mentioning
confidence: 99%